Absolute eosinophil count predicts clinical outcomes and toxicity in non-small cell lung cancer patients treated with immunotherapy. (2022) - Caliman, Enrico; Fancelli, Sara; Ottanelli, Carlotta; Mazzoni, Francesca; Paglialunga, Luca; Lavacchi, Daniele; Michelet, Marta Rita Gatta; Giommoni, Elisa; Napolitano, Brunella; Scolari, Federico; Voltolini, Luca; Comin, Camilla Eva; et al.
Highlights: AEC is a peripheral blood parameter routinely available in clinical practice. AEC ≥130/μL in NSCLC patients treated with ICIs correlated with longer PFS and OS. AEC increased significantly after the first doses of ICI therapy. High-AEC group had a higher risk of developing irAEs during treatment. IrAEs is an independent prognostic factor for better clinical outcomes. Abstract: Objectives: Immune checkpoint inhibitors (ICIs) have led to a paradigm shift in non-small cell lung cancer (NSCLC) treatment. We investigated absolute eosinophil count (AEC) as a predictor of clinical outcomes and toxicity in NSCLC patients receiving ICIs. Materials and Methods: AEC was retrospectively collected at baseline and during treatment from 158 advanced NSCLC patients treated with single agent anti-PD1/anti-PDL1 monoclonal antibody in first or subsequent line of therapy at Medical Oncology Unit, Careggi University Hospital, Florence (Italy), between January 2016 to October 2020. Results: We found a significant association between high baseline AEC (≥130/μL) and better clinical outcomes. The response rates were 64.4% and 35.6% for patients with high and low AEC, respectively ( p = 0.009). The high-AEC group showed a significantly longer PFS and OS than the low-AEC group (mPFS = 7.0 months, 95% CI 5.0–10.0 vs 2.5 months, 95% CI 2.0–4.0, p = 0.007 and mOS = 9.0 months, CI 95% 7.0–15.0 vs 5.5 months, 95% CI 4.0–8.0, p = 0.009, respectively). An increased risk of immune-related adverse events (irAEs) was reported in the high-AEC group ( p = 0.133). IrAEs resulted an independent prognostic factor for both better outcomes (mPFS = 8.0 months, 95% CI 7.0–12.0 vs 2.0 months, 95% CI 2.0–3.0, p <0.001; mOS = 13.0 months 95% CI 9.0–19.0 vs 4.0 months 95% CI 3.0–6–0, p <0.001) and response to ICIs (response rate = 33.8% vs 14.9%, disease control rate = 72.0% vs 32.1%, p <0.001). Conclusion: High baseline AEC value (≥130/μL) is a predictive biomarker of clinical benefit and irAEs occurrence in NSCLC patients treated with ICIs.